Implementasi Model Cooperative Learning Jigsaw dalam Pembelajaran PAI di SMK - Aryani, Wiwik Dyah; Mustakim, Asep; Kurnia, Indri; Soraya, Siti; Maesaroh, Maesaroh (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2025)
This study aims to evaluate the implementation of the Cooperative Learning model, specifically the Jigsaw type, in Islamic Religious Education (PAI) lessons for Grade X TKJ 2 at SMK YADIKA Tanjungsari, Sumedang Regency, during the 2024/2025 academic year. A descriptive qualitative method was employed, with data collected through observation, interviews, and documentation. The results reveal that the jigsaw model enhances student engagement through active group discussions, peer teaching, and collaborative learning. Key supporting factors include student enthusiasm and the teacher’s role as an active facilitator. However, several challenges emerged, such as limited class time, the ineffectiveness of online learning, and students’ varying abilities in comprehending and delivering material. In conclusion, the Jigsaw-type Cooperative Learning model proves effective in improving the quality of PAI instruction, although further strategies are required to optimize its application, particularly in blended learning contexts.ABSTRAKPenelitian ini bertujuan untuk mengevaluasi implementasi model pembelajaran Cooperative Learning Jigsaw dalam mata pelajaran Pendidikan Agama Islam (PAI) di kelas X TKJ 2 SMK YADIKA Tanjungsari Kabupaten Sumedang pada Tahun Ajaran 2024/2025. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa penerapan model jigsaw mampu meningkatkan keterlibatan siswa dalam pembelajaran melalui kegiatan diskusi kelompok yang aktif, penyampaian materi oleh siswa, serta kerja sama antaranggota kelompok. Faktor pendukung utama adalah antusiasme siswa dan peran aktif guru sebagai fasilitator. Sementara itu, hambatan yang dihadapi meliputi keterbatasan waktu, pembelajaran daring yang kurang efektif, serta variasi kemampuan siswa dalam memahami dan menyampaikan materi. Kesimpulannya, model Cooperative Learning Jigsaw efektif dalam meningkatkan kualitas pembelajaran PAI, namun diperlukan strategi lanjutan untuk mengoptimalkan implementasinya, terutama dalam konteks blended learning.